SERANGAN DAN KERUSAKAN TANAMAN CENGKEH YANG DISEBABKAN OLEH Hexamitodera semivelutina Hell. DI DESA RERER KABUPATEN MINAHASA - Runaweri, Christian; Pelealu, J.; Manueke, J. (Universitas Sam Ratulangi, 2017)
ABSTRACT The aim of this research is to know the attack and damage of clove stem borer Hexamitodera semivelutina at some elevation in Rerer village of Kombi sub-district of Minahasa Regencyfor 2 months (February - April 2017). The research was conducted by survey on farmers’ clove plantation area. The research was using a stratified random sampling method with observing the incidence and severity of H. semivelutina pest of clove plant. Treadment using 3 stratum height of place from sea level that is 0 - <300 meters from sea level (mfsl), 300 - <600 (mfsl), and >600 (mfsl). The result of this research are the symptom of attack and damage of clove plant caused by H. Semivelutina pest as follows : incidence rate and severity according to altitude of place 0 - <300 mfsl are 24.67% and 12.55%, while at height 300 - <600 mfsl are 42.34% and 22.88 %, and at altitude> 600 mfsl are 61.67% and 33.66%.Keywords : incidence of pest, severity of pest, Hexamitodera semivelutina